Transition Metal-Free Synthesis of meta-Bromo- and meta-Trifluoromethylanilines from Cyclopentanones by a Cascade Reaction - Staudt, Markus; Çetin, Adnan; Bunch, Lennart (Wiley-V C H Verlag Gmbh, 2022)
Anilines are key constituents in biologically active compounds and often obtained from transition metal-catalyzed coupling of an aryl halide with an amine. In this work, we report a transition metal-free method for the synthesis of meta-bromo- and meta-trifluoromethylanilines starting from 3-tribromomethylcyclopentanone or 3-(2-bromo-2-chloro-1,1,1-trifluoroethyl)cyclopentanone, respectively. The scope of the transformation is shown by application of primary, secondary and aromatic amines. The reaction proceeds in acceptable to high yields (20-81 %), and allows for the synthesis of anilines with substitution patterns otherwise difficult to access.
Keywords: anilines; drug synthesis; electrocyclic ring-opening; new methodology; transition metal-free; Catalyzed C-N; Conversion